‘A Different Ball Game’: Engaging Men from Rural and Lower Socioeconomic Areas in Behavioural Weight Management Interventions - McDonald, Matthew David (Curtin University, 2023)
Men in lower socioeconomic rural areas are at higher risk of ill-health but less likely to participate in preventative health interventions than rural women. This thesis highlights that a greater consideration of socioeconomic factors in weight management interventions for men is required. Then, provides a case example for how a metropolitan program can be adapted with rural stakeholders, and offers insights into how popular local sports can help engage rural men in health interventions.